2020
DOI: 10.3390/ijerph17051505
|View full text |Cite
|
Sign up to set email alerts
|

Application and Perceived Effectiveness of Complementary and Alternative Intervention Strategies for Attention-Deficit/Hyperactivity Disorder: Relationships with Affiliate Stigma

Abstract: This cross-sectional questionnaire survey study was designed to examine the complementary and alternative intervention strategies (CAIS) employed by caregivers for their children’s attention-deficit/hyperactivity disorder (ADHD) and the associations of affiliate stigma with the employment and rated effectiveness of these strategies in Taiwan. A total of 400 caregivers of children with ADHD participated. CAIS that the caregivers employed and their effectiveness rated by the caregivers were surveyed. Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
(43 reference statements)
0
5
0
2
Order By: Relevance
“…Caregivers with higher parenting stress in the DC domain perceived greater CADHD’s difficulties in self-regulation and fulfillment of their obligations [ 13 ]. Studies have found that AS is related to caregivers’ unfavorable attitudes toward clinical diagnoses and treatment for ADHD [ 19 , 20 , 21 ]. The timing of proper treatment for ADHD may be delayed, and children’s ADHD symptoms and difficulties in daily lives could be aggravated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers with higher parenting stress in the DC domain perceived greater CADHD’s difficulties in self-regulation and fulfillment of their obligations [ 13 ]. Studies have found that AS is related to caregivers’ unfavorable attitudes toward clinical diagnoses and treatment for ADHD [ 19 , 20 , 21 ]. The timing of proper treatment for ADHD may be delayed, and children’s ADHD symptoms and difficulties in daily lives could be aggravated.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study on 159 French mothers of boys with ADHD, Charbonnier et al found that mothers’ distress was positively related with AS [ 15 ]. Another cross-sectional study on 400 Taiwanese caregivers of CADHD found that AS is related to caregiver depression [ 18 ] and to unfavorable attitudes toward clinical diagnoses, treatment, and etiological explanations for ADHD [ 19 , 20 , 21 ]. In addition, AS was reported to prospectively predict emotional problems and physical discomfort in Taiwanese CADHD one year later [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, caregivers with affiliate stigma may distance themselves from their children with ADHD to avoid feeling shame [ 1 ]; therefore, children may not receive sufficient psychological support to properly develop emotional regulation. Third, caregivers with strong affiliate stigma tend to attribute their children’s ADHD to nonbiological etiologies [ 39 ] and employ intervention programs that lack credibility [ 40 ]. Children’s ADHD symptoms may not be treated adequately and consequently impair multiple dimensions of children’s functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Para Chou et al (2020), o efeito foi positivo para 68% dos participantes da pesquisa, Souza, Ferreira Neto e Pereira (2021) ressaltaram que a técnica se torna ainda mais potente quando surge como auxílio no tratamento psicoterapêutico, facilitando a mediação do psicólogo, observou ainda, melhora na socialização com outras crianças, bem como a interação com os familiares. Vale pontuar que a técnica ideal a ser utilizada é a de Musicoterapia Ativa e deve ser executada por profissional qualificado que se baseia em evidência científica, visto que o leque de diferentes estímulos que a música pode proporcionar, se não utilizada adequadamente, podem gerar efeitos negativos (SANTOS et al, 2022).…”
Section: Musicoterapiaunclassified